ShO‘RTAN GAZ-KIMYO MAJMUASI FAOLIYATINING HUDUD ATROFIDA TARQALGAN TUPROQLARNING UNUMDORLIGIGA TA’SIRI - Safarov, A.A.; Toshmuradova, M.Sh. (SCIENCE and SOCIETY, 2025)
This article presents some information on the contamination of soils with heavy metals and changes in the ecological state of settlements as a result of the activities of the Shurtan gas chemical complex.
Keywords: Shurtan gas chemical complex; soil; heavy metals; pollution; ecological state; soil fertility; agriculture; food